1989
DOI: 10.1002/aja.1001860307
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology and morphometry of the nasal fossae of four species of North American shrews (Soricinae)

Abstract: The present study compares the morphology of the nasal conchae and the relative development (i.e., surface area and neurosensory cell number) of the olfactory epithelium between four species of shrews occupying different ecotopes (Blarina brevicauda, Sorex cinereus, S. fumeus, S. palustris). The number of olfactory cells was corrected for split cell error. Data were analyzed by using size indices based on the allometric method. The convoluted shape of the maxilloturbinal in Blarina, with large respiratory epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
7
30
0
Order By: Relevance
“…Our study confirms previous work demonstrating a reduction in olfactory organ size (defined in various ways) and presumed olfactory ability in semi-terrestrial and aquatic mammals, including some shrews (Sorex palustris; Larochelle & Baron, 1989), fissipeds (Ferron, 1973;Gittleman, 1991), pinnipeds, monotremes, and insectivores (Pihlströ m et al 2005;Pihlströ m, 2008). Some of these studies used osteological proxies for olfactory ability, including cribriform (ethmoid) plate area and olfactory bulb endocast size, and others estimated olfactory epithelial surface area from serial sections of whole heads.…”
Section: Linearsupporting
confidence: 81%
“…Our study confirms previous work demonstrating a reduction in olfactory organ size (defined in various ways) and presumed olfactory ability in semi-terrestrial and aquatic mammals, including some shrews (Sorex palustris; Larochelle & Baron, 1989), fissipeds (Ferron, 1973;Gittleman, 1991), pinnipeds, monotremes, and insectivores (Pihlströ m et al 2005;Pihlströ m, 2008). Some of these studies used osteological proxies for olfactory ability, including cribriform (ethmoid) plate area and olfactory bulb endocast size, and others estimated olfactory epithelial surface area from serial sections of whole heads.…”
Section: Linearsupporting
confidence: 81%
“…In at least some insectivores, an osseous turbinal is adjacent to the lateral nasal gland duct (see Fig. 1 in LaRochelle and Baron, 1989). More problematic is the large anteriorly positioned osseous turbinal in rodents, commonly identified as the nasoturbinal (Adams, 1972;Clancy et al, 1994;Jurcisek et al, 2003), which is directly continuous with the ossified nasal tectum.…”
Section: Nasoturbinalmentioning
confidence: 99%
“…Comparative studies on the sensitivity of the olfactory organ seem to indicate that threshold values increase with increasing receptor density (Sigmund 1985;Sigmund and Sedlacek 1985). Morphological studies on the olfactory mucosa, however, have shown that receptor density in semiaquatic species is similar to that in terrestrial shrews (Sollner and Kraft 1980;Larochelle and Baron 1989b), despite poorer olfactory capacity as indicated by reduction of the peripheral and central olfactory structures.…”
Section: Main Olfactory Systemmentioning
confidence: 94%
“…(1957), Woehrmann-Repenning (1975), and Woehrmann- Repenning and Meinel (1977). The size of the respiratory and olfactory regions of the epithelium was determined by Gurtovoi (1966) in Sorex araneus; by Sollner and Kraft (1980) in Sorex araneus, S. minutus, and Neomys fodiens; by Sigmund (1985) and Sigmund and Sedlacek (1985) in Sorex araneus; and by and Larochelle and Baron (1989b) in Sorex cinereus, S. fumeus, S. palustris, and Blarina brevicauda. Larochelle and Baron reviewed the earlier literature and showed that in terrestrial Soricinae the surface of the olfactory epithelium makes up between 62.6% and 69.3% of the total nasal epithelium; in wateradapted species, such as Sorex palustris and Neomys fodiens, the corresponding figures are 52.2% and 41.1 %, respectively.…”
Section: Physiology Sense Organsmentioning
confidence: 99%